Assessment of self-care practices among hypertensive patients: a clinic based study in rural area of Singur, West Bengal - Dasgupta, Aparajita; Sembiah, Sembagamuthu; Paul, Bobby; Ghosh, Ayon; Biswas, Bijit; Mallick, Nazrul (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension, also known as high blood pressure is a global public health concern. It is an important modifiable risk factor for cardiovascular disease and stroke. It remains silent, being generally asymptomatic during its clinical course and it accounts for a large proportion of cardiovascular deaths; lifestyle modification is the first line of intervention for all patients with hypertension, yet it was never been empirical. The aim of the study was to assess the pattern of self-care practices, if any and also to find out the factors associated with it, among the hypertensive patients in the outpatient department. Methods: A clinic-based, observational, cross-sectional study was conducted at health center under RHU & TC, Singur, which is the rural field practice area of All India Institute of Hygiene and Public Health, Kolkata among 124 hypertensive subjects. Binary logistic regression was done to find out the factors associated with the self-care practices using SPSS software. Results: In the present study, 62.9% of study participants suffering from hypertension had unfavourable self-care practices. Logistic regression showed age above 60 years (OR-3.1), primary level education (OR-5.6), poor socio economic status (OR-2.4), widow/separated (OR-3.3) and people with self-perceived poor health status (OR-2.8)had significant association with unfavourable self-care practices. After adjusting with other variables, age (AOR-2.3) and education (AOR-3.8) remained significant predictor of outcome. Conclusions: The findings revealed that the self-care practices among hypertensive patients were unfavourable in rural area. This calls for a deep need in increasing the awareness about healthy lifestyle among hypertensive patients. This study provides key elements to affect policy changes and social interventions.